KINERJA ORGANISASI BIDANG PENGELOLAAN ASET DAERAH BADAN KEUANGAN DAERAH KABUPATEN SEMARANG DALAM PENGELOLAAN ASET TETAP - Izzat, Alfian Noor; Mustam, Mochammad (Journal of Public Policy and Management Review, 2018)
Regional autonomy as a momentum underlying local independence in the management of local fixed assets,but many autonomous regions including the Government of Semarang Regency are not yet optimal in managing their owned assets. The purpose of this research is to describe the organization's performance in Asset Management Division of Regional Finance Agency (BKUD) Semarang Regency in the management of fixed assets.This research uses descriptive qualitative research design. The informants in thisresearch were heads of regional asset management, three heads of sub-division of asset management, staff and some communities. Data collection techniques is by interview, observation, documentation. Performance appraisal in this research use four indicator that is Accountability, Effectiveness, Efficiency and Transparency. Based on the results of research, it can be concluded that the organizational performance of the Regional Asset Management Division of Regional Finance Agency of Semarang Regency in the management of fixed assets needs to be improved again. This is because there are still some obstacles in the management of fixed assets such as, weak coordination of the Regional Asset Management Division with other OPD, has no fixed asset storage, still lack of transparency, low staff numbers and low staff competence, inadequate facilities and infrastructure. Suggestion given by the researcher is improvement of continuous coordination with external parties (OPD-OPD, BPN, and Village Government related to land certification process), the addition of competent human resources, organizing staff training on IT, looking for alternative place for asset storage, improve transparency, and procurement of additional facilities and infrastructure.